Educators' subjective experiences of workplace bullying within a perceived neoliberalist education system - Lynette Jacobs; Kevin LG Teise (South African Journal of Education, 2019)
Teachers in South Africa experience exceptionally high levels of bullying in the workplace, in particular, bullying that relates to their profession. As research has shown that the organisational culture can either inhibit or promote bullying, in this paper we consider the possibility that neoliberalism creates an environment for workplace bullying to thrive. Based on unstructured interviews with 4 educators, we draw parallels between what they subjectively perceived as workplace bullying within the hierarchal structure of the school and school system and the ideology of neoliberalism. The value of this study lies in the awareness that it could raise among managers in the education system of how the system actually influences their mind-set and actions.